The Effect of Work Discipline and Work Motivation on Performance Mediated by Work Stress on Indonesian Air Force Personnel at The Education Squadron 105 Adisutjipto Air Force Base - Sanaji Sanaji; Arief Subyantoro; Yuni Siswanti (Journal of International Conference Proceedings, 2021)
This research is research quantitative descriptive which aims to determine and analyze the effect of work discipline and work motivation on performance mediated by work stress on Indonesian Air Force personnel at the Education Squadron 105 Adisucipto Air Force Base. The research was conducted by distributing questionnaires to Indonesian Air Force personnel at the Education Squadron 105 Adisucipto Air Force Base, totaling 41 people. The questionnaires were returned and filled in completely, then processed using path analysis and Sobel test. Test the instrument using the Pearson product moment formula and test the reliability by looking at the Cronbach's Alpha coefficient. The results of hypothesis testing indicate that there is an effect of work discipline on the performance of Indonesian Air Force personnel at the Education Squadron 105 Adisucipto Air Force Base. Work motivation effects the performance of Indonesian Air Force personnel at the Education Squadron 105 Adisucipto Air Force Base. Work stress effects the performance of Indonesian Air Force personnel at the Education Squadron 105 Adisucipto Air Force Base. Work discipline has an effect on performance mediated by work stress on Indonesian Air Force personnel at the Education Squadron 105 Adisucipto Air Force Base. Work motivation has an effect on performance mediated by work stress on Indonesian Air Force personnel at the Education Squadron 105 Adisucipto Air Force Base. The results of this study provide theoretical, methodological, and managerial contributions as well as recommendations for further research to explore other variables that can affect performance, in addition to work discipline, work motivation and work stress.